Hydrodeoxygenation of oxidized distilled bio-oil for the production of gasoline fuel type. (15th March 2016) - Luo, Yan; Guda, Vamshi Krishna; Hassan, El Barbary; Steele, Philip H.; Mitchell, Brian; Yu, Fei
Highlights: Oxidation had more influence on the yield of total hydrocarbons than distillation. The highest total hydrocarbon yield was obtained from oxidized distilled bio-oil. The 2nd-stage hydrocarbons were in the range of gasoline fuel boiling points. The main products for upgrading of oxidized bio-oil were aliphatic hydrocarbons. The main products for upgrading of non-oxidized bio-oil were aromatic hydrocarbons. Abstract: Distilled and oxidized distilled bio-oils were subjected to 1st-stage mild hydrodeoxygenation and 2nd-stage full hydrodeoxygenation using nickel/silica–alumina catalyst as a means to enhance hydrocarbon yield. Raw bio-oil was treated for hydrodeoxygenation as a control to which to compare study treatments. Following two-stage hydrodeoxygenation, four types of hydrocarbons were mainly comprised of gasoline and had water contents, oxygen contents and total acid numbers of nearly zero and higher heating values of 44–45 MJ/kg. Total hydrocarbon yields for raw bio-oil, oxidized raw bio-oil, distilled bio-oil and oxidized distilled bio-oil were 11.6, 16.2, 12.9 and 20.5 wt.%, respectively. The results indicated that oxidation had the most influence on increasing the yield of gasoline fuel type followed by distillation. Gas chromatography/mass spectrometry characterization showed that 66.0–76.6% of aliphatic hydrocarbons and 19.5–31.6% of aromatic hydrocarbons were the main products for oxidized bio-oils while 35.5–38.7% of aliphatic hydrocarbons and 58.2–63.1% of aromatic hydrocarbons were the main products for non-oxidized bio-oils. Both aliphatic and aromatic hydrocarbons are important components for liquid transportation fuels and chemical products.